Predictive Relationship Between School Culture and Student Union Leadership Involvement in Security on Lecturers' Job Delivery - Ogedi Peter Okoli; Nwachinemere James Paul (Fakultas Pertanian, 2026)
The study Predictive relationship between school culture and student union leadership involvement in security on lecturers' job delivery adopted a quantitative research approach with a focus on correlational design. The population for the study comprises 738 respondents, comprising 688 lecturers from the faculty of education and 50 postgraduate student union leaders. Taro Yamane's mathematical estimation multi-stage sampling technique was used to determine the sample size of 292 respondents (272 lecturers and 20 union leaders). School Culture Questionnaire (SCQ), Student Union Leadership Questionnaire (SULQ) and Lecturers' Job Delivery Questionnaire (LJDQ) were used for data collection. SCQ, SULQ, and LJDQ were validated by three experts. Internal consistency of the questionnaire was determined using the Cronbach alpha statistic, which yielded an index of .83 for SCQ, .79 for SULQ and .77 for LJDQ. Data was analysed using PPMCC, and the f-ratio at a 0.05 level of significance. The findings show that school culture significantly to a high positive extent relate to lecturers' job delivery in public universities in the South East, Nigeria, and the relationship between school culture and lecturers' job delivery is statistically significant. In conclusion, both factors of school culture and students' union leadership involvement in the school security committee are essential predictors of lecturers' job delivery in public universities in the South-East, Nigeria. The study recommends that the National Universities Commission (NUC) should, through policy directives and supervision, develop positive school culture and shared values in Nigerian universities in order to promote teaching excellence, student engagement, and academic achievement for improved job delivery amongst lecturers.